Cruel Brittania: a personal critique of nursing in the United Kingdom - Watson, R.; Shields, Linda (eContent Management, 2009)
The United Kingdom (UK) once led the world in nursing but because of the exigencies of the funding mechanisms of the National Health Service (NHS), it has fallen a long way behind other countries. We aim to raise the awareness inside and outside the UK about the decline in nursing as a profession there. We are purposely contentious, in an attempt to raise questions, both for the UK and for countries which are recruiting British nurses who are leaving because of job losses caused by the funding crisis in the NHS. This paper discusses where the problems that have led to the decline have come from, where nursing is going and poses questions for the future. We hope that the UK government and those who influence the development of nursing will bring it back to the standard it once had.